Competitive pattern of global tin products trade from the perspective of industry chain - Jin, Yuning; Dai, Tao (Frontiers in Earth Science, 2025)
With the application of tin in photovoltaic power generation, new energy vehicles, and other emerging industries, the contradiction between the supply and demand of tin resources has become increasingly prominent, which further exacerbates the competition between tin resource importing and exporting countries. According to the global trade data from 2002 to 2022, this paper classifies five kinds of tin-containing products into three commodity types, namely, upstream, midstream, and downstream, and constructs the international trade network, import competition network, and export competition network. This paper selects key competitive countries and relationships, examines the characteristics of specific communities, and analyzes the network’s structural features and evolution patterns over time. The results showed that: (1) The distribution of the intensity of competition in tin products is very uneven, the trend of oligopoly in upstream product competition is obvious, and the competition in midstream and downstream products is getting more and more intense. (2) The tin industry chain has developed a tripartite pattern of import competition in Asia, Europe, and North America. Developed countries primarily compete in midstream tin products, while developing countries focus on importing upstream and downstream tin products. (3) The export competition for tin products is primarily concentrated in Asia, with Malaysia losing its centrality and Myanmar, Indonesia, and China gaining the centrality. (4) The competition communication in upstream tin products is more evident than in midstream and downstream products, and their stability is stronger. The above analysis can help countries identify their trade competitors and provide suggestions for finding new partners.